2023
DOI: 10.3390/s23020980
|View full text |Cite
|
Sign up to set email alerts
|

A THD-Based Fault Protection Method Using MSOGI-FLL Grid Voltage Estimator

Abstract: The rapid growth of the distributed generators (DGs) integration into the distribution systems (DSs) creates new technical issues; conventional relay settings need to be updated depending on the network topology and operational mode as fault protection a major challenge. This emphasizes the need for new fault protection methods to ensure secure protection and prevent undesirable tripping. Total harmonic distortion (THD) is an important indicator for assessing the quality of the grid. Here, a new protection sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…According to [ 36 , 43 ], the SOGI-FLL and FFT methods were implemented into a DSP, and the computational burden was computed in the number of processor cycles (c) used to compute the SOGI, the FLL, and the FFT blocks. In [ 43 ], it was reported that the SOGI needs 149c, the FLL 49c, and the FFT 7019c per phase.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to [ 36 , 43 ], the SOGI-FLL and FFT methods were implemented into a DSP, and the computational burden was computed in the number of processor cycles (c) used to compute the SOGI, the FLL, and the FFT blocks. In [ 43 ], it was reported that the SOGI needs 149c, the FLL 49c, and the FFT 7019c per phase.…”
Section: Resultsmentioning
confidence: 99%
“…The method described in [ 36 ] is used to obtain the harmonic components of the grid in order to calculate the THD. In [ 36 ], an MSOGI is employed together with a Frequency Locked-Loop (MSOGI-FLL) to obtain the fundamental and the 3rd, 6th, and 9th harmonics of the grid voltages.…”
Section: Thd Measurement Methodsmentioning
confidence: 99%
See 3 more Smart Citations